Prevalence of surgical site infections post-cesarean section in Saudi Arabia: A systematic review and meta-analysis - Najim Z. Alshahrani; Abdulrahman M. Albeshry; Mohammed A. Aljunaid; Mohammed A. Kilani (Journal of Infection and Public Health)
This systematic review and meta-analysis evaluated the prevalence, risk factors, and outcomes of surgical site infections (SSIs) following cesarean sections (C/S) in Saudi Arabia, a significant public health concern impacting maternal morbidity and hospital stays. Seven studies, including 7632 women, were analyzed. The pooled prevalence of SSIs post-cesarean section was 3 % (95 % CI: 2 %–4 %), with substantial heterogeneity across studies (I² = 81.8 %). Consistently identified risk factors included Pre-existing diabetes mellitus, Obesity (BMI ≥ 30), and prolonged surgery duration, while hypertension, premature rupture of membranes, and gestational age showed no significant association with SSIs. Most infections were managed effectively with systemic antibiotics, and maternal outcomes were generally favorable, although some cases required prolonged recovery or neonatal intensive care admission. Staphylococcus aureus and Escherichia coli were among the most common causative pathogens. These findings underscore the need for enhanced preventive strategies and standardized protocols to reduce SSI rates and improve maternal and neonatal health outcomes in Saudi Arabia.